Progressive and disseminated histoplasma infection and hemophagocytic lymphohistiocytosis in an immunocompetent adult. Issue 5 (27th March 2019) - Dousa, Khalid M.; De la Hoz, Alejandro; Church, Elizabeth; Onger, Tiffany; Perez, Federico; Saade, Elie
Key Clinical Message: Hemophagocytic lymphohistiocytosis (HLH) in adults is a life‐threatening underdiagnosed disorder that complicates different infectious syndromes and overlaps with sepsis. No guidelines are available for the management of HLH in adults. A high index of suspicion is required in patients with disseminated histoplasmosis. Abstract : Hemophagocytic lymphohistiocytosis (HLH) in adults is a life‐threatening underdiagnosed disorder that complicates different infectious syndromes and overlaps with sepsis. No guidelines are available for the management of HLH in adults. A high index of suspicion is required in patients with disseminated histoplasmosis.